Baron Žiga Zios in njegova zbirka mineralov - Faninger, Ernest (Scopolia, 1983)
The present article deals with the origin of the family of the Zoises, the arrival of Michelangelo Zois (1694-1777) to Ljubljana and his vertiginous social rise to a contractor, landed proprietor and a baron. There follow biographical data on his son, Baron Sigmund Zois (1747-1819), a great patron of the Englighment and a renowned natural scientist. He is dealt with primarily as a mineralogist and a geologist. His mineralogical collection, oneof the greatest of its kind in the then Europe, represents the foundation stone of the first Slovene museum. After Sigmund Zois a mineral has been named, i.e. zoisite. The illustrations of particular historical significance are accompanied by detailed commentaries.
Keywords: Mineralogija; mineralogy; Slovenia; Slovenija; zbirke; Zois